Transport Properties and Related Thermodynamic Data of Binary Mixtures - Dong, Qian (autor) (Design Institute of Physical Property Data, American Institute of Chemical Engineers)
Contenido: Tablas: Propiedades críticas; Densidad; Coeficiente de difusión; Solubilidad; tensión superficial; Conductividad térmica; Viscosidad; Apéndice.